2019
DOI: 10.1111/jorc.12271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived organisational justice on job satisfaction and burnout levels of haemodialysis nurses

Abstract: L. (2019). The effect of perceived organisational justice on job satisfaction and burnout levels of haemodialysis nurses. Journal of Renal Care XX(XX),1-9. S U M M A R YBackground: Organisational justice influences job satisfaction, the performance of individuals and the functioning of institutions.The lack of evidence-based studies investigating the relationship between hemodialysis nurses' perceptions of organisational justice, job satisfaction and burnout has created a research gap in this area. Objective:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…Moreover, the correlation between the three subscales in this study suggested that the nurses who were emotionally exhausted also feel depersonalization and reduced personal accomplishment, which was consistent to the previous study 31 . The emotional exhaustion and personal accomplishment levels in this study were lower than those found by Trbojević‐Stanković et al 32 and higher than the results of Topbas et al 33 but similar to those obtained by other researchers 20,34 . The reasons for the differences among the studies may be as follows: first, the sample size could affect the significance level of the correlations; second, the various structures and policies of different organizations as well as different religious, spiritual and/or moral values could have resulted in different results.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the correlation between the three subscales in this study suggested that the nurses who were emotionally exhausted also feel depersonalization and reduced personal accomplishment, which was consistent to the previous study 31 . The emotional exhaustion and personal accomplishment levels in this study were lower than those found by Trbojević‐Stanković et al 32 and higher than the results of Topbas et al 33 but similar to those obtained by other researchers 20,34 . The reasons for the differences among the studies may be as follows: first, the sample size could affect the significance level of the correlations; second, the various structures and policies of different organizations as well as different religious, spiritual and/or moral values could have resulted in different results.…”
Section: Discussionsupporting
confidence: 90%
“…Although the work environment in haemodialysis units seems to be rated as positive and healthy, the burnout levels among dialysis nurses remain high (Hayes, Bonner et al, 2015). The dialysis nurses' work environment characteristics, such as workload and the organisational justice, have been recognized as a major contributing factor to both overall stress and burnout, which is associated with poor patient satisfaction (Argentero et al, 2008; Lewis et al, 1992; Topbaş et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…RNs' high organizational justice has been positively associated with job satisfaction (Chegini et al, 2019; Faheem & Mahmud, 2015; Negahban et al, 2017; Topbas et al, 2019) and has been found to increase job satisfaction and, through this, reduce intentions for early retirement (Koponen et al, 2016). One study showed a lack of correlation between organizational justice and job satisfaction (Elliot et al, 2017).…”
Section: Resultsmentioning
confidence: 99%